A cost comparison of amikacin therapy with bedaquiline, for drug-resistant tuberculosis in the UK. Issue 1 (January 2020) - Manalan, Kavina; Green, Nathan; Arnold, Amber; Cooke, Graham S.; Dedicoat, Martin; Lipman, Marc; Loyse, Angela; Harrison, Tom S.; Kon, Onn Min
Highlights: The WHO in 2018 replaced the injectable agents with bedaquiline for drug-resistant tuberculosis. Bedaquiline does not require intravenous administration and may reduce culture conversion time. The cost of bedaquiline in the UK is close to cost neutral compared to injectable amikacin. Abstract: Objectives: Prioritisation of oral bedaquiline over the injectable agents in the treatment of multidrug-resistant Tuberculosis (MDR-TB) in the World Health Organisations (WHO) 2019 guidelines prompted this UK analysis of cost implications. The objective was to estimate the costs of amikacin versus bedaquiline in MDR TB treatment regimens using a historical cohort where the injectable agents were the standard of care. Methods: This was a retrospective study using a known cohort of UK patients treated with an injectable agent, with data available on resource use, costs for the use of amikacin were compared with those for bedaquiline, based on recommended monitoring for bedaquiline. Results: The estimated cost of treatment per patient had mean (sd) of £27, 236 (4952) for the observed injectable group, £30, 264 (3392) and 36, 309 (3901) for the 6 and 8 month amikacin groups, and £31, 760 (2092) for the bedaquiline group. The cost in the bedaquiline group was £30, 772 (1855) with a 10% reduction and £27, 079 (1234) with a 33% reduction in-patient stay. Conclusions: In most scenarios, bedaquiline is close to cost neutral compared with injectable therapy, especially if, as expected, some reduction in duration of admission is possible as a result of bedaquiline's more rapid culture conversion.